Methods For Developing Physical Preparedness Of Young Football Players At The Initial Training Stage - N.A.Kaypov (Periodica Journal, 2024)
The article is about the methods of one year cycle in the training process of young football players on the preparation stage
Keywords: physical education; cycle; loading; experiment